Marketing Strategy Proposal for Increasing Customer Loyalty of Agnes Monica - Pascaline, Melvina; Purwanegara, Mustika Sufiati; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2013)
Agnes Monica is a famous celebrity from Indonesia who has the quality and inspiring many young people. She is a singer, actress, presenter, and also brand endorser at once who has achieved many prestigious awards during her 20 years experience in entertainment industry. She is now pursuing her dream to be an international singer which then insists her to spend lots of time in USA. The management see the threat as there will be the lack of product availability and will cause brand switching. Build a strong emotional engagement with customers to the high level of loyalty, in this case her fans, is considered to mitigate this threat. This is the main objective of this study. The data used was generated by interview to 15 fanclub members for at least three years and online questionnaire to 380 fans. Industry analysis, competitor analysis, customer analysis, marketing mix analysis, personal branding analysis, customer based brand equity analysis, and brand community relationship analysis were completed to find the root causes. Root causes from the data and analysis are segment augmentation, lack of internet promotion, bad opinion for her originality, and the weak relationship between the customers and company. This study give solutions to each root causes found and all solutions are inter-related to overcome it. Company hopes given solutions will gain enhancement of Agnes Monicaâ€™s value, so that strong fans loyalty will built. This study provides two scenario as solution for company and scheduled for 12 months in 2013. Second scenario is more affordable than first scenario, but still aims escalation of fans loyalty. Budget for scenario one is Rp. 734,500,000 while scenario two is Rp. 412,500,000.Â Keyword: customer loyalty, brand relationship, personality branding